PENERAPAN MODEL PEMBELAJARAN IMPROVE UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN IKATAN KIMIA DI KELAS X MIA MAN 1 PEKANBARU - Geni Chintia Dasmi; Johni Azmi; Erviyenni Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: The research aims to determine whether the application of the improve learning model to improve student learning achievement on the subject of chemical bonds in the class x MIA MAN 1 pekanbaru. The type of this research is experimental research with randomized control group pretest-posttest design. Sample of research is X MIA 2 as the experimental class, X MIA 1 as the control class.control class and experimental class normality test using Liliefors test and homogeneity test using equality of two average test. The experimental group was treated implementation of IMPROVE while the control group without implementation of IMPROVE. T-test right side was used as analysis technique. Based on the data analysis obtained tcount>ttable is 4,084 > 1,667,meaning that the application of the improve learning model to improve student learning achievement on the subject of chemical bonds in the class x MIA MAN 1 pekanbaru Key Words: IMPROVE, Learning achievement, chemical bonds